UPAYA MENINGKATKAN HASIL BELAJAR SISWA KELAS VIII B MENGGUNAKAN MEDIA LUMIO BY SMART DALAM PEMBELAJARAN IPS - Sejati, Muhammad Daffa Firzatullah Kstaria; Ratnawati, Nurul (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The use of learning media in learning activities, especially in social studies subjects, is expected to overcome existing challenges, such as low student learning outcomes in lessons and difficulties in understanding the material. In this digital era, the development of information technology offers a variety of learning media that can be used to support the teaching and learning process. One of the increasingly popular learning media is Lumio by smart. This research model is PTK (Classroom Action Research) with the teacher as the researcher. The presence of the researcher is very important because the researcher acts as the teacher. Data collection techniques in this study used observation, tests and documentation. Data collection was carried out by giving questionnaires to expert media validators and material experts. The use of Lumio by smart learning media in social studies subjects for class VIII has a good impact on efforts to improve student learning outcomes, this is indicated by an increase in the percentage of student learning outcome completion during 2 learning cycles. In cycle I, it was found that the student completion rate reached 36% then increased in cycle II by 70%. The results of these data indicate that Lumio by smart learning media can improve social studies learning outcomes for class VIII.